Insight into the role of dermal white adipose tissue loss in dermal fibrosis. Issue 1 (5th October 2021) - Liu, Si‐Yu; Wu, Jun‐Jie; Chen, Zhong‐Hua; Zou, Ming‐Li; Teng, Ying‐Ying; Zhang, Kai‐Wen; Li, Yue‐Yue; Guo, Dang‐Yang; Yuan, Feng‐Lai; Li, Xia
Abstract: The loss of dermal white adipose tissue (dWAT) is vital to the formation of dermal fibrosis (DF), but the specific mechanism is not well understood. A few studies are reviewed to explore the role of dWAT in the formation of DF. Recent findings indicated that the adipocytes‐to‐myofibroblasts transition in dWAT reflects the direct contribution to the DF formation. While adipose‐derived stem cells (ADSCs) contained in dWAT express antifibrotic cytokines, the loss of ADSCs leads to skin protection decreased, which indirectly exacerbates DF and tissue damage. Therefore, blocking or reversing the adipocytes‐to‐myofibroblasts transition or improving the survival of ADSCs in dWAT and the expression of antifibrotic cytokines may be an effective strategy for the treatment of DF. Abstract : The loss of adipocytes in dermal white adipose tissue (dWAT) reflects the direct contribution to dermal fibrosis. While the loss of adipose‐derived stem cells (ADSCs) in dWAT reflect indirect contribution to the development of DF. The loss of dWAT was accompanied with ADSCs paracrine antifibrosis function reduced.